Arabic Language In Companies And Institutions: Manifestations And Treatment/ المخالفات اللغوية لدى الشركات والمؤسسات: المظاهر والعلاج - Khalid Hassan Alabri (Ijaz Arabi Journal of Arabic Learning, 2022)
No one is characterized by perfection except for God. Therefore, human error is a natural matter, and one of these errors is the linguistic error: as it is a common mistake and may happen to individuals. However, it becomes humiliating when it is repeated over and over again. This becomes more embarrassing if a company repeats the linguistic error or an institute of several departments with experienced and qualified staff. This paper highlights some forms and manifestations of linguistic errors in official institutions and major companies in the Kingdom of Saudi Arabia. The indication of the effects of a linguistic error in changing the meaning or understanding the context; the paper also touches on the most significant causes of language weakness in companies and institutions and then the means of treating these language weaknesses. The causes of language errors are employees leaving Arabic, spoken and written, and lack of interest from entities. Whether government or not, the belief of some company owners that what is related to Arabic is a matter of formality and is not essential, the negative impact of some media underestimating the correct language, and a weak desire to master the language. The solution is to appoint a linguistic auditor in the institutions to review the integrity of the writing.